Ethics, archives and data sharing in qualitative research. Issue 5 (20th August 2020) - McLeod, Julie; O'Connor, Kate
Abstract: This article investigates dilemmas in the archiving and sharing of qualitative data in educational research, critically engaging with practices and debates from across the social sciences. Ethical, epistemological and methodological challenges are examined in reference to open access agendas, the politics of knowledge production, and transformations in research practices in the era of data management. We first consider practical and interpretive decisions in archiving qualitative data, then map current policy and regulatory frameworks governing research data management, taking Australia as a case-study. We argue that governance and protocols for data sharing have not attended sufficiently to the distinctive ethical and methodological dimensions and knowledge claims of qualitative research. Instead, approaches associated with quantitative data are extrapolated in ways which construct an imaginary of decontextualised data, abstracted from the conditions of its production. We further argue for more critical attention to the double-edged affordances and ambivalent effects of data sharing and openness and to how data archives are imagined, constructed and curated. This includes greater acknowledgement of the affective and temporal dynamics involved in data archiving, understanding them as practices of (re)invention that also curate 'archives for the future' and help to foster an historicising imaginary in educational research.